ASEAN ECONOMIC COMMUNITY: BALANCING INVESTMENT AND SOCIO-ECONOMIC RIGHTS - James Reinaldo Rumpia (Muhammadiyah Law Review Journal, 2018)
ASEAN Economic Community (AEC) promotes the development and economic welfare in ASEAN nation. Indonesia, on the other side, accept it as a big chance of investment. Through investment, the government hopes to achieve economic development. Policies, regulation, even deregulation has been made for a friendly investment. But, there is no guaranteed investment will also bring social welfare. Regulation not only as a tool for investment but also to protect socio-economic rights of people's. As the example, the regulation made for protecting the local worker, or employment opportunities. The regulation also provided for protection and  empowerment for small and middle economies or the poverty alleviation.  This condition will be the dilemma for the government to balance the investment and to fulfill socio-economic rights at the same time. Truly are UUDNRI 1945 already formulate to solve this dilemma. We can learn from article 33 UUDNRI 1945, about the idea to keep it economic development work together in harmony with the will to fulfill socio-economic rights. This paper focuses on seeing how regulation consistence in fulfills socio-economic rights in AEC Free Trade, with the normative method through legislation, social, and economic approach, The research result describe the regulations used for facing AEC dominate by investment design and forgot about socio-economic rights.